Mercury's cross‐tail current sheet: Structure, X‐line location and stress balance. Issue 2 (27th January 2017) - Poh, Gangkai; Slavin, James A.; Jia, Xianzhe; Raines, Jim M.; Imber, Suzanne M.; Sun, Wei‐Jie; Gershman, Daniel J.; DiBraccio, Gina A.; Genestreti, Kevin J.; Smith, Andy W.
Abstract: The structure, X‐line location, and magnetohydrodynamic (MHD) stress balance of Mercury's magnetotail were examined between −2.6 <  X MSM  < −1.4 R M using MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) measurements from 319 central plasma sheet (CPS) crossings. The mean plasma β in the CPS calculated from MESSENGER data is ~ 6. The CPS magnetic field was southward (i.e., tailward of X‐line) ~ 2–18% of the time. Extrapolation of downtail variations in BZ indicates an average X‐line location at −3 R M . Modeling of magnetic field measurements produced a cross‐tail current sheet (CS) thickness, current density, and inner CS edge location of 0.39 R M, 92 nA/m 2 and −1.22 R M, respectively. Application of MHD stress balance suggests that heavy planetary ions may be important in maintaining stress balance within Mercury's CPS. Qualitative similarities between Mercury's and Earth's magnetotail are remarkable given the differences in upstream conditions, internal plasma composition, finite gyro‐radius scaling, and Mercury's lack of ionosphere. Key Points: Physical properties of Mercury's cross‐tail current sheet are more intense but similar to Earth's Inner edge of cross‐tail current sheet and mean NMNL location are found to be ~1.2 and −3 R M Stress balance seems to require significant contributions from heavy planetary ions and/or H + anisotropy